Seminars in the process of studying the discipline «Organization and methods of improving physical culture» - Марченко, С. І. (Physical Education Theory and Methodology, 2014)
The purpose of research — to develop a program of seminars course «Organization and methods of improving physical training» for the educational qualification of 6.01020101 — bachelor. Methods of research — the study of literature, software and normative documents, theoretical analysis and synthesis of the literature data, a systematic approach. The main results of the study. The concept of classes of the course «Organization and methods of Physical Culture» is in the system presenting the material, which allows to form students’ knowledge, skills and practical skills necessary physical education teachers to organize and conduct various forms of fitness training.